Transcriptional and post‐transcriptional limitations of high‐yielding, PEI‐mediated transient transfection with CHO and HEK‐293E cells. (26th February 2015) - Rajendra, Yashas; Kiseljak, Divor; Baldi, Lucia; Wurm, Florian M.; Hacker, David L.
<x xml:space="preserve">Abstract</x> Transient gene expression (TGE) in human embryonic kidney (HEK‐293) and Chinese hamster ovary (CHO) cells is a well‐established technology for the rapid generation of recombinant proteins. Although the maximum TGE yields have reached 1 g/L or more, the amount of plasmid DNA (pDNA) required for transfection remains high. Although greater than 103 copies of pDNA are present per transfected cell, protein yields are still lower than those achieved in recombinant cell lines with only one or a few copies of the transgene. This indicates a clear limitation to TGE in terms of the maximum level of recombinant protein production. In this study, we investigated the limitations to high‐yielding TGE processes with CHO and HEK‐293E cells using a monoclonal antibody as a model protein. For either cell host, both the intracellular and intranuclear pDNA levels increased linearly with the amount of pDNA added to the culture. In contrast, transgene mRNA accumulation reached a plateau as the intranuclear pDNA amount increased, suggesting a limitation in pDNA transcription. A post‐transcriptional limitation to TGE yields was revealed by calculating the amount of antibody produced per transgene mRNA (mRNA utilization). For both hosts the transgene mRNA utilization decreased dramatically when transfected pDNA amounts increased beyond the level giving the maximum protein yield. The post‐transcriptional limitation did not appear to be due to bottlenecks in antibody assembly or secretion, suggesting that transgene mRNA translation may be limiting. The results show that TGE yields are not limited by pDNA delivery into the nuclei, but in pDNA and transgene mRNA utilization. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 31:541–549, 2015